(3QSGdI JfbjM GdCHMGK ddedd GdKdGKs - (3SYO Hf efUhQ Hf SYO Hf GdMSf Hf gHI Gddg Hf cehfI GdGSQGFjdj, YR GdOhdI,J (B676 (3g` s
(3ChdgG (B:s
(3hHYO aEfg bO LQJ eaGhVGJ GbJVJ Cf YedJ gPg GdebGdI ai JfbjM GdCHMGK ddedd GdKdGK s
(3BNQgG (B:s
(3hef Gddg JYGdi CSFdI GdgOGjI hGdYUeI hMSf GdNGJeI hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B214s
(3eUOQ GbJfGA GdCUd (B:s
(3MSjf Ydi eMahX (B_ (3HZOGO (B(1/114) s
Keywords: (3GdJhMjO hGdedd hGdfMds